Implementation of DSP based algorithms for impedance measurements - Ramos, Pedro M. (2009)
In this paper, two DSP based algorithms are implemented for impedance measurements. The algorithms (the seven-parameter sine-fitting algorithm and the ellipse fitting algorithm) are implemented and tested in a commercial DSP kit. The complete system is used to compare the algorithms by measuring 105 different impedances, using the four-wire impedance measurement method. The strategic selection of appropriate reference impedances, intrinsic to the impedance measurement method, is also described. The results of each algorithm are compared in terms of speed and accuracy. This is the ground work for a portable DSP based impedance measurement device to be implemented in specifically designed hardware.